Georgia : Technical Assistance Report-External Sector Statistics Mission. (IMF Staff Country Reports; Country Report ;, 2019)
This Technical Assistance report on Georgia highlights the external sector statistics (ESS). The main objectives of the mission were to assess the Geostat's progress in the area of ESS and provide further recommendations on improving the data collection and compilation for producing the financial account components, including direct investment statistics, in an integrated format. With the mission's assistance and based on the analysis' results, a method has been agreed for filling the gaps in coverage of imported cars and for addressing the limitations in valuation of re-exported cars. The mission stressed the need for improving the coverage of transactions related to gambling that have shown a growing trend in recent years, with increasing nonresidents' activities. With the increasing workload due to the compilation and dissemination of new products or to enhancing the coverage and quality of existing products, and bearing in mind the staff turnover, there is need to consider allocating additional staff to the External Trade and Foreign Investments Statistics Department. In order to support progress, the mission recommended a detailed one-year action plan, with priority recommendations carrying weight to make headway in improving Georgia's ESS.